对比语言视角下汉柬语“饮食类”动词研究 - KOK MENG SEAK (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2026)
From a syntactic perspective, both Chinese and Khmer are typical subject-verb-object (SVO) languages, and thus their linguistic features often exhibit a degree of symmetry. However, this study conducts a comparative analysis of the usage of